Saying “I Don’t Know”: A Video-Based Study on Physicians’ Claims of No-Knowledge in Assisted Reproductive Technology Consultations - Menichetti, Julia; Gerwing, Jennifer; Borghi, Lidia; Gulbrandsen, Pål; Vegni, Elena (Frontiers in Psychology, 2021)
Introduction The assisted reproductive technology (ART) field deals with consistent and predictable gaps in knowledge. Expressing lack of knowledge with a sentence like “I don’t know” can be challenging for doctors. This study examined physicians’ negative epistemic disclaimer “non lo so” in Italian ART doctor-couple interactions. In particular, it aimed to reveal specific features of “non lo so”: function, topic, temporality, responsibility, and interactional aspects. Methods This was a video-based observational study. We used microanalysis of face-to-face dialogue to analyze 20 purposively selected triadic consultations from a corpus of 85. This inductive analysis focused on the function, the content (topic and temporality) and some selected interactional aspects of the “non lo so”, quantifying and capturing the interaction between these qualitative features. Results We found 82 doctors’ “non lo so” in the corpus (mean = 4.4; range = 0–15). We discovered three main functions of this expression: propositional (n = 73/82), relational (n = 6/82), discursive (n = 3/82). The most frequent topics raising doctors’ “non lo so” were costs (n = 11/82), treatment-related aspects (n = 10/82), and timing issues (n = 9/82). In more than half of the cases (n = 44/82), present issues emerged. The majority (n = 70/82) of “non lo so” was framed using the “I,” with doctors’ taking personal responsibility. Patients played a role in these expressions from doctors: Patients initiated more than one third of them, and in one fourth of the cases, patients followed up immediately. Conclusion Our findings may be related to characteristics of the specific field of ART. Doctors in this setting must frequently express a direct lack of knowledge to their patients, and when they do, they mean it literally. Patients contribute to such disclosures, and their responses suggest that they find them acceptable, showing that they may expect limitations in their potential to conceive.